Aggregate production planning model based on mixed integer linear programming - Uluçamlı, Veli (Öneri Dergisi, 2010)
This work presents a mixed integer linear programming method developed by using 0-1 variables for solving aggregate production planning problem with the following performance criteria: (1) maximize profit, (2) minimize costs. The production planning activities are called as aggregate production planning when both it is produced more than one goods and the demand changes period by period. The purpose of aggregate production planning is not to prepare detailed plans for each goods, it is to do plans for whole goods produced in the firm together to take in hand. Aggregate production planning is probably one of the most important, yet least understood, jobs that a manager performs. However, all parts of the organization, operations, marketing, finance, and so on, must work together in the planning process to ensure that they are moving in harmony with one another. Aggregate production planning is such a method that can move all parts of the organizations in same harmony.
Karma tamsayılı doğrusal programlama yöntemi ile bütünleşik üretim planlaması
Keywords: Aggregate Production Planning, 0–1 Variables, Mixed Integer Linear Programming. - Bütünleşik Üretim Planlaması, 0–1 Değişkenleri, Karma Tamsayılı Doğrusal Programlama